1971
DOI: 10.1038/icb.1971.67
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Transfer of Immunoglobulin Into Mammary Secretion of Cows

Abstract: Summary. Changes in the concentration of IgG^. IgC,, IgM, IgA and albumin in semm and mammary secretion were studied in 15 cows and 2 heifers before and after parturition. Concentrations of IgGj and IgC, in blood serum 3-5 weeks before parturition were 13-38 ± 0-75 and 10-08 ±: 0 39 mg/ml (means ± S.E.) respectively. In all animaLs tlie cfinc-entration of IgC, in serum decreased abruptly, usually by more than 50%, 2-3 weeks before parturition, and during the same period the concentrations of IgC2, IgM, IgA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
2
11

Year Published

1973
1973
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(134 citation statements)
references
References 6 publications
(12 reference statements)
9
109
2
11
Order By: Relevance
“…The selective index for IgA in parotid saliva is not significantly different from that obtained for milk from non-immunized glands of ewes in mid-lactation (Watson and Lascelles, 1973), whereas the higher selective index for IgA in milk from immunized glands of these ewes was significantly lower than that obtained for non-parotid saliva. This lends support to our earlier suggestion (Watson and Lascelles, 1971) that, whereas the non-parotid salivary glands are being subjected constantly to antigenie stimulation, the continuous flow of large quantities of parotid saliva ensures that the parotid gland receives relatively little local antigenie stimulation.…”
Section: Secretionsupporting
confidence: 72%
See 1 more Smart Citation
“…The selective index for IgA in parotid saliva is not significantly different from that obtained for milk from non-immunized glands of ewes in mid-lactation (Watson and Lascelles, 1973), whereas the higher selective index for IgA in milk from immunized glands of these ewes was significantly lower than that obtained for non-parotid saliva. This lends support to our earlier suggestion (Watson and Lascelles, 1971) that, whereas the non-parotid salivary glands are being subjected constantly to antigenie stimulation, the continuous flow of large quantities of parotid saliva ensures that the parotid gland receives relatively little local antigenie stimulation.…”
Section: Secretionsupporting
confidence: 72%
“…Brandon, Watson and Lascelles, 1971). The selective indices for IgGj were around 2 for both parotid and non-parotid glands, which is similar to results obtained for the lactating mammary gland by Mackenzie and Lascelles (1968) who measured the distribution of i^ii-labelled IgGj^ and IgG2 between blood and milk in lactating ewes.…”
Section: Concentrations Of Immunoglobulins and Albumin In Parotid Andsupporting
confidence: 71%
“…Concentrations of the immunoglobulins IgGh IgGz, IgM and 19A in lamb plasma and colostral whey were determined as described by Brandon et al (1971) using the single radial immunodiffusion technique (Mancini et al 1965).…”
Section: Analysis Of Samplesmentioning
confidence: 99%
“…The IgG1 displays unique characteristics: a) it constitutes 90% of the colostral immunoglobulins, providing neonatal protection as well as instructions for the action of the immune system. (Butler et al, 1972;Butler et al, 1974;Guidry et al, 1980); b) it is selectively transported by the FcRn, a receptor which is found in the lung alveolar and mammary gland epithelium (Dyxon et al, 1961;Kemler et al, 1965;Brandon et al, 1971); c) it binds to neutrophils such as IgG2 (Mcguire et al, 1979;Butler et al, 1985); d) it is synthesized locally and released as a secretory immunoglobulin on the mucosa (Brandon et al, 1971;Butler et al, 1985). Different allotypes among animals of the same species correspond to the capacity of influencing the immune system and/or creating resistance to viral and bacterial infections.…”
Section: Introductionmentioning
confidence: 99%